Short communication: Genetic analysis of lactation curves in buffaloes, using Wood’s model - Carvalho, Ludmilla A. Marques de; Moura, Guilherme F. de; Vieira, Dheynne A.; Hurtado-Lugo, Naudin A.; Aspilcueta-Borquis, Rusbel R.; Gomide, Ana P. C.; Tonhati, Humberto; Oliveira, Henrique N. de; Araujo-Neto, Francisco R. de (Spanish Journal of Agricultural Research, 2020)
Aim of study: To estimate the heritability and genetic correlations for lactation curve traits in buffaloes.Area of study: The buffalo cows were raised on properties located in the states of São Paulo, Ceará and Rio Grande do Norte, Brazil.Material and methods: The individual parameters of Wood’s model ( , , and ) were obtained using a non-linear mixed model. Peak yield (PY), peak time (PT) and lactation persistency (LP) were also calculated. These individual parameters were employed in multi-trait analysis with the milk yield (MY) using Bayesian inference.Main results: The heritability estimates were of low to moderate magnitudes, with values ranging from 0.156 ( ) to 0.299 (PY). The estimates for genetic correlation between the Wood’s parameters and MY were of low to high magnitude and ranged from -0.533 (  and MY) to 0.983 (PY and MY).Research highlights: The heritability estimates obtained indicate that the traits studied can be used in animal breeding programs.